2021
DOI: 10.1021/acs.jpcc.1c02119
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Effect of UV-Light-Induced “Burn-in” Degradation in Non-Fullerene Acceptor Based Organic Solar Cells

Abstract: Rapid degradation of bulk heterojunction (BHJ) organic solar cells employing non-fullerene acceptor molecules, especially during the initial period of operation (“burn-in”), poses a major challenge. Among the prominent factors causing rapid deterioration of device performance, such as light and thermal stress, UV-induced degradation is shown to significantly reduce the lifetime. It is observed that UV-exposed devices exhibit the sharpest decrease in the performance parameters during the burn-in period. Systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Among prominent deterioration factors, UV-induced degradation played a significant role to reduce the device's lifetime. [31,32] Jeong et al suggested an approach by employing the UV-cut filter (UCF) in the front side of OSCs that blocks the incident light below 403 nm wavelength, and the resultant devices exhibited slow photoinduced degradation as compared to without (w/o) UCF. [33] The devices with filter and w/o filter retain ∼90% and ∼20% of the initial value after 14 hrs of continuous illumination under reduced intensity (air mass [AM] 1.5G, 80 mW/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among prominent deterioration factors, UV-induced degradation played a significant role to reduce the device's lifetime. [31,32] Jeong et al suggested an approach by employing the UV-cut filter (UCF) in the front side of OSCs that blocks the incident light below 403 nm wavelength, and the resultant devices exhibited slow photoinduced degradation as compared to without (w/o) UCF. [33] The devices with filter and w/o filter retain ∼90% and ∼20% of the initial value after 14 hrs of continuous illumination under reduced intensity (air mass [AM] 1.5G, 80 mW/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among prominent deterioration factors, UV‐induced degradation played a significant role to reduce the device's lifetime. [ 31 , 32 ] Jeong et al. suggested an approach by employing the UV‐cut filter (UCF) in the front side of OSCs that blocks the incident light below 403 nm wavelength, and the resultant devices exhibited slow photoinduced degradation as compared to without (w/o) UCF.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its low cost, easy synthesis, and simple solution processability makes it industrially viable. , Despite these advantages, ZnO ETL is photocatalytically active, which leads to decomposition and photooxidation of organic molecules (e.g., NFA) on the surface of ZnO, via redox reactions and formation of hydroxyl radicals . This, subsequently, leads to charge accumulation and recombination at the ZnO interface, which both strongly reduce the device stability. ,, Various approaches have been explored to control such interfacial degradation: Su and co-workers utilized nitrogen and sulfur-doped graphene oxide nanosheets (NS-GNSs) as a modifier layer for ZnO; Hu et al used aqueous polyethylenimine as a modifier layer; Liu et al developed modified ZnO layers, Me–ZnO, DMSO-ZnO, and sol–gel-ZnO; and Xu et al used C60 self-assembled monolayer (SAM) as a protective buffer layer . Recently, Aryal et al demonstrated that 2D Mxene could be embedded with ZnO to reduce this photocatalytic decomposition on ZnO surface .…”
Section: Introductionmentioning
confidence: 99%
“…31 This, subsequently, leads to charge accumulation and recombination at the ZnO interface, which both strongly reduce the device stability. 29,34,35 Various approaches have been explored to control such interfacial degradation: Su and co-workers 36 utilized nitrogen and sulfur-doped graphene oxide nanosheets (NS-GNSs) as a modifier layer for ZnO; Hu et al 37 used aqueous polyethylenimine as a modifier layer; Liu et al 38 developed modified ZnO layers, Me−ZnO, DMSO-ZnO, and sol−gel-ZnO; and Xu et al used C60 self-assembled monolayer (SAM) as a protective buffer layer. 39 Recently, Aryal et al demonstrated that 2D Mxene could be embedded with ZnO to reduce this photocatalytic decomposition on ZnO surface.…”
Section: Introductionmentioning
confidence: 99%
“…The inverted solar cells’ stability and efficiency were increased most noticeably by the above approaches. High-energy UV radiation can cause the disintegration of the conjugated materials in the active layer via photolysis, resulting in the formation of trap states and, thus, causing instability and performance decay in the OSCs, , in particular for nonfullerene-acceptor (NFA)-based solar cells. Due to the unique structure of the inverted solar cell, where the highly transmissive ZnO is on the side of the transparent electrode, some of the harmful UV can still reach the active layer.…”
Section: Introductionmentioning
confidence: 99%